Antiferromagnetic resonance of polycrystalline BiMn2O5 - Santana, V. T. [UNESP]; Walmsley, L. [UNESP]; Fier, I. [UNESP]; Eichel, R. -A.; Jakes, P.; Chumak, I.; Ozarowski, A.; van Tol, J.; Nascimento, O. R. (Elsevier B.V., 2015)
Multi-frequency electron spin resonance (ESR) measurements in polycrystalline samples of BiMn2O5 were employed to observe antiferromagnetic resonances (AFMR) in the range 0-14 A below the Neel temperature. The experimental data were analyzed using the phenomenological theory of Yosida and Nagamiya. Three resonance modes were identified in the xz (ac) plane from the data at 5 K. Macroscopic constants of anisotropy K-1 = 12.5 x 10(6) erg/cm(3) and K-2 = 7.0 x 10(6) erg/cm(3) were calculated allowing for the single-site anisotropy constant K'to be estimated at T=0 K. The obtained value shows reasonable agreement with theoretical predictions.
Keywords: Multiferroics; Magnetic anisotropy; Antiferromagnetic resonance